Pengaruh Related Party Transaction, Thin Capitalization dan Firm Size Terhadap Penghindaran Pajak - Sb, T. Nur'din Rizki; Rahmadani; Toruan, Heddy Lumban; Hidayat, Akmal; Kurniati, Endang (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study examines the effect of related party transactions, thin capitalization, and firm size on tax avoidance in non-cyclical consumer manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The research population consists of 125 companies, and the sample was determined using purposive sampling based on specific criteria, resulting in 24 companies with a total of 120 firm-year observations. The research variables include related party transactions, thin capitalization, and firm size as independent variables, while tax avoidance serves as the dependent variable. Data were analyzed using panel data regression with EViews 12. The results show that related party transactions have a significant positive effect on tax avoidance, while thin capitalization and firm size do not have a significant effect. These findings imply that companies tend to utilize affiliate transactions as a strategy to reduce tax obligations, whereas capital structure and firm size do not play a decisive role. The results highlight the importance of strengthening tax regulations and supervision to minimize the use of related party transactions as tools for tax avoidance. Future research is recommended to include additional variables and expand the sample scope across sectors to obtain more generalizable results.